Pertuzumab plus trastuzumab for HER2-amplified metastatic colorectal cancer (MyPathway): an updated report from a multicentre, open-label, phase 2a, multiple basket study. Issue 4 (April 2019) - Meric-Bernstam, Funda; Hurwitz, Herbert; Raghav, Kanwal Pratap Singh; McWilliams, Robert R; Fakih, Marwan; VanderWalde, Ari; Swanton, Charles; Kurzrock, Razelle; Burris, Howard; Sweeney, Christopher; Bose, Ron; Spigel, David R; et al.
Summary: Background: Therapies targeting HER2 have improved clinical outcomes in HER2-positive breast and gastric cancers, and are emerging as potential treatments for HER2-positive metastatic colorectal cancer. MyPathway evaluates the activity of targeted therapies in non-indicated tumour types with potentially predictive molecular alterations. We aimed to assess the activity of pertuzumab and trastuzumab in patients with HER2 -amplified metastatic colorectal cancer. Methods: MyPathway is an ongoing, phase 2a, multiple basket study. Patients in this subset analysis were aged 18 years or older and had treatment-refractory, histologically confirmed HER2 -amplified metastatic colorectal cancer with measurable or evaluable disease and an Eastern Cooperative Oncology Group performance status score of 2 or less, enrolled from 25 hospitals or clinics in 16 states of the USA. Patients received pertuzumab (840 mg loading dose, then 420 mg every 3 weeks, intravenously) and trastuzumab (8 mg/kg loading dose, then 6 mg/kg every 3 weeks, intravenously). The primary endpoint was the proportion of patients who achieved an objective response based on investigator-reported tumour responses. Analyses were done per protocol. This ongoing trial is registered withClinicalTrials.gov, numberNCT02091141 . Findings: Between Oct 20, 2014, and June 22, 2017, 57 patients with HER2 -amplified metastatic colorectal cancer were enrolled in the MyPathway study and deemed eligible for inclusionin this cohort analysis. Among these 57 evaluable patients, as of Aug 1, 2017, one (2%) patient had a complete response and 17 (30%) had partial responses; thus overall 18 of 57 patients achieved an objective response (32%, 95% CI 20–45). The most common treatment-emergent adverse events were diarrhoea (19 [33%] of 57 patients), fatigue (18 [32%] patients), and nausea (17 [30%] patients). Grade 3–4 treatment-emergent adverse events were recorded in 21 (37%) of 57 patients, most commonly hypokalaemia and abdominal pain (each three [5%] patients). Serious treatment-emergent adverse events were reported in ten (18%) patients and two (4%) of these adverse events (ie, chills and infusion-related reaction) were considered treatment related. There were no treatment-related deaths. Interpretation: Dual HER2-targeted therapy with pertuzumab plus trastuzumab is well tolerated and could represent a therapeutic opportunity for patients with heavily pretreated, HER2 -amplified metastatic colorectal cancer. Funding: F Hoffmann-La Roche/Genentech.